Micromineral Content of Swiss Chard (Beta vulgaris L. var. cicla) Leaves Grown on Zeolite-Amended Sandy Soil - Sindesi, Olwetu Antonia; Ncube, Bongani; Lewu, Muinat Nike; Mulidzi, Azwimbavhi Reckson; Lewu, Francis Bayo (Talenta Publisher, 2022)
Swiss chard (Beta vulgaris L. var. cicla), a popular leafy vegetable grown mainly for its ease of production and nutritional content, is normally used as a good source of microminerals iron (Fe) and zinc (Zn). Improving plant uptake of Fe and Zn could assist in reducing micromineral deficiencies in humans, which are a global problem. A greenhouse pot experiment was conducted at the Agricultural Research Council, Stellenbosch to assess the response in micromineral and soil trace elements uptake in Swiss chard grown under zeolite and sandy soil. The experiment consisted of four treatments, with six replicates arranged in a randomized complete block design. Zeolite was applied at 0%; 10%; 20% and 30% in combination with sandy soil. Swiss chard was harvested for micromineral analysis 143 days after transplanting. Soil samples were also collected at the end of each growing season. Swiss chard leaves were analysed for Fe, Zn, Mn, and Cu content with soil samples also analysed for the same elements. The study found that zeolite did not improve Swiss chard uptake of Fe, Zn and Mn. Soil Fe also had an inverse relationship to zeolite application while the residual effect of zeolite showed the same trend, but only in the second season. This study indicated that zeolite cannot be used to improve micromineral uptake by Swiss chard but can be used to rectify heavy metal-infested soils.